Assessing Learning Management System success in the UAE universities: how quality measures linked to students' academic performance - Aldabbas, Hazem; Elamin, Abdallah M.; Ahmed, Ahmed Z. E.; Gernal, Liza (Frontiers in Education, 2025)
Learning Management Systems (LMS) have become widely recognized tools for university learning worldwide and identifying the factors affecting students' academic performance has always been a major focus in both academia and practice. This study aims to develop a research model based on the Delone and McLean Information System Success Model to investigate the effects of quality measures on students' perceived usefulness, satisfaction, actual usage, and academic performance. Data collected from 118 business school students at two universities in the United Arab Emirates (UAE) were analyzed using the PLS-SEM approach to validate the research model. The data analysis revealed that eight combined quality measures have a positive and significant effect on students' perceived usefulness, perceived satisfaction, and actual use. In turn, each factor—perceived usefulness, perceived satisfaction, and actual use—has a positive and significant impact on students' academic performance. Further, we find that the following impact factors (perceived usefulness, perceived satisfaction, and actual use) mediate the relationship between quality measures and students' academic performance. Interestingly, this group of four variables—quality measures, perceived usefulness, perceived satisfaction, and actual usage—explains 84.9% of students' overall academic performance. Therefore, educational institutions seeking to achieve greater benefits from LMS should pay considerable attention to quality measures that directly impact students' usefulness, satisfaction, and actual usage, ultimately resulting in improved academic performance. These factors play a significant role in enhancing the overall quality of LMS and university education in the UAE and potentially in other countries as well.